(untitled) (Revista BOEM, 2025)
This paper presents a study that aimed to understand how future Mathematics teachers, in initial formation, have been understanding the teaching of this area of knowledge, based on what has been produced in the formative path, when they turn to think about teaching situations. Guided by the question ‘What do the teaching situations developed by the undergraduate students in Mathematics at UTFPR-CT say about the teaching of Mathematics?’. The teaching situations aimed at Early Childhood Education and Elementary School 1 and 2, produced during the initial training of undergraduate students in Mathematics at the Federal Technological University of Paraná, Curitiba campus (UTFPR-CT), were inventoried and analyzed from a phenomenological perspective. From this analysis, convergences found with the curricular matrices of the aforementioned initial formation, as one of the pillars that support choices for pedagogical proposals. The collection of productions, called teaching situations, was done personal contact and via e-mail with the academics and teachers responsible for the disciplines, programs and projects associated with the course that resulted in the development of these work intentions. This study showed that the most used teaching methodologies were Problem Solving, Mathematical Investigation and Games. The most frequently covered mathematical contents were Geometry and Statistics.